Rome Bureau
Radio Free Europe ran a special information bureau in Rome in order to keep up to date with political and diplomatic developments in the Vatican and in Italy. The bureau collected news agency reports and articles mainly from the Italian press,as well as reports by Western news agencies. Some of the official communiqués of the Vatican can also be found among the documents. The series contains official Vatican press releases, news agency reports and articles from the Italian and English-language press that relate to the diplomatic relationship between the Vatican and Hungary, Poland, Czechoslovakia, Ukraine and the Soviet Union. The documents of the Synod of Bishops are also filed in this part of the collection. The description of the documents dealing with Vatican-Hungarian affairs is more detailed, and highlights certain developments that deserve special attention. This is due to the unique political conflicts surrounding the Church in Hungary in the post-1956 era. Special focus falls on Cardinal József Mindszenty, archbishop of Esztergom, who took refuge in the U.S. Embassy in Budapest in 1956. The issue of his removal from his official position and his subsequent fate caused lasting diplomatic tension between the U.S. and Hungary as well as between Hungary and the Vatican. Press documents, mostly articles and reports from the Italian press cover the activities of the Red Brigades, the violent extreme left-wing terrorist group in Italy, and political developments within and around the Italian Communist Party. Special attention was devoted to the PCI-Soviet relationship. Press and court documents relate to and cover the attempted assassination of John Paul II by an assailant of Turkish origin, Ali Agca, in 1981. The documents are divided into three sections. Italian and English press documents on the attack itself, subsequent events and the trial of Ali Agca. Press reports and articles, mainly from the Italian press, that cover the supposed involvement of the Bulgarian secret service in the attack and press reports on the trial of the alleged Bulgarian secret agent Antonov and his accomplices and records of the verdict of the Tribunal in Rome that tried Antonov`s case. Documents collected by the RFE Rome Bureau deal with human rights issues in the Soviet Bloc in the light of the agreements of the “third basket" of the 1975 Helsinki Treaty. The documents are divided into two sections: human rights issues in the Soviet Union; and documents related to the second 'Sakharov Hearings’ held in Rome, 26-29, November 1977. The idea of the 'Sakharov Hearings’ emerged soon after the human rights clauses of the Helsinki Treaty were signed in 1975. The hearings followed the pattern of the famous 'Vietnam Hearings’ organized by Bertrand Russell and other influential Western intellectuals roughly a decade earlier, with the intention of uncovering and discussing the alleged war crimes committed by the U.S. Army during the Vietnam war. For the 'Sakharov Hearings’ a committee of prominent intellectuals from the West and the East was set up in order to discuss the violations of the human right clauses of the Helsinki Treaty that took place in the Soviet bloc. The procedure, as in the case of the 'Vietnam Hearings’, took the form of a court trial. The first session of the 'Sakharov Hearings’ took place in Stockholm in 1976, the second session was held in Rome in November 1977. Some of the documents (Human Rights in the Soviet Union) would appear to belong to the first session of the 'Sakharov Hearings’, though this is not explicitly stated. Documents from the second session in Rome were collected and filed by the RFE Rome Bureau. The Commission used reports (Documents) as well as testimonies (Witnesses, Testimonianze), which are filed separately. Accruals not expected